2009
DOI: 10.1208/s12248-009-9146-8
|View full text |Cite
|
Sign up to set email alerts
|

Herb–Drug Interactions with St John’s Wort (Hypericum perforatum): an Update on Clinical Observations

Abstract: Abstract. St John's wort (SJW) extracts, prepared from the aerial parts of Hypericum perforatum, contain numerous pharmacologically active ingredients, including naphthodianthrones (e.g., hypericin and its derivatives), phloroglucinols derivatives (e.g., hyperforin, which inhibits the reuptake of a number of neurotransmitters, including serotonin), and flavonoids. Such extracts are widely used for the treatment of mild-to-moderate depression. As a monotherapy, SJW has an encouraging safety profile. However, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
192
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(202 citation statements)
references
References 119 publications
0
192
0
10
Order By: Relevance
“…66 In addition, serotonin syndrome and hypomania have been reported when SJW is used concurrently with antidepressants. 67,68 SJW is recommended as first-line monotherapy in mild to moderate MDD (Level 1 Evidence) and is recommended as a second-line adjunctive treatment for moderate to severe MDD (Level 2 Evidence) ( Table 3). …”
Section: Natural Health Productsmentioning
confidence: 99%
“…66 In addition, serotonin syndrome and hypomania have been reported when SJW is used concurrently with antidepressants. 67,68 SJW is recommended as first-line monotherapy in mild to moderate MDD (Level 1 Evidence) and is recommended as a second-line adjunctive treatment for moderate to severe MDD (Level 2 Evidence) ( Table 3). …”
Section: Natural Health Productsmentioning
confidence: 99%
“…SJW has been shown to cause some dramatic interactions mainly as a result of its ability to induce CYP3A4, 2E1, 2C9 and P glycoproteins. 19 Examples of significant drug-SJW interactions include reducing cyclosporine and tacrolimus levels, which in some cases has resulted in transplant rejections, reducing the effectiveness of oral contraceptives causing unintended pregnancies, and studies demonstrate reduced levels and effective ness of warfarin, digoxin, methadone and some benzo diazepines. 19 It would be advisable to monitor carefully most other drugs when faced with a patient using SJW and consider alternative antidepressant choices.…”
Section: St John's Wortmentioning
confidence: 99%
“…Other drugs interfering with St. John's wort CYP 3A4 induction include , oral contraceptives.and indinavir (156). Literature review of 128 case reports or case series, and 80 clinical trials have revealed that St John's wort-induced cytochrome P450 and P-glycoprotein induction, decreases plasma levels of a large variety and frequently used medications.…”
Section: Wwwintechopencommentioning
confidence: 99%